Inter-cluster synchronization scheme for femtocell network - Hasan, M.K.; Saeed, Rashid Abdelhaleem; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Islam, Shayla; Nafi, Nazmus Shaker (2012)
Femtocell is for indoor coverage, and cannot use a GPS antenna for time synchronization. High-precision crystal oscillators can solve the timing problem, but they are often too expensive for consumer grade devices. Since fBS and macrocell Base Station (mBS) network operate on the same frequency under a licensed spectrum fBS network can interfere with the macrocell network. In addition, fBSs can also interfere with each other if multiple units are in close proximity. In some cases, conflicting base stations may simultaneously raise transmit power in order to improve signal quality, thereby creating some interference. Furthermore, in a flat fBS structured network using IEEE 1588 synchronization algorithm and fBS-fBS synchronization scheme creates offset and frequency error which results inaccurate synchronization. However, in this paper an inter-cluster synchronization scheme is proposed in order to reduce offset and frequency error (skew) to achieve precise synchronization in fBS neighbor nodes. The analytical result shows that the proposed scheme is able to reduce the offset and skew significantly through inter-cluster synchronization ultimately increases synchronization accuracy. Therefore, achieved synchronization accuracy is 90% higher than the existing MS-assisted schemes.